A new species of Anemonefish from French Polynesia, Amphiprion maohiensis, (Pomacentridae, Amphiprioninae), the Polynesian anemonefish - James L. O’Donnell; Ricardo Beldade; Jason Johns; Giacomo Bernardi (ZooKeys, 2025)
Anemonefishes (Teleostei, Pomacentridae) comprise approximately 28 species of damselfishes that exclusively live symbiotically with sea anemones. Distribution ranges vary, with some species only found in few isolated islands and others with ranges that span almost the entire Indo-Pacific. The orange-fin anemonefish, Amphiprion chrysopterus shows a wide distribution, from Australia to French Polynesia, extending north to Micronesia and the Marshall Islands. Two main color morphs exist, with a morph that displays a white tail and a second morph that has an orange tail. In French Polynesia, only the orange-tail morph is present, while in the rest of the range, the white-tail morph is prevalent, while the orange-tail morph is also present, but very uncommon. Here we assessed the potential presence of a cryptic species in French Polynesia based on morphology, mitochondrial markers, and full genome sequencing. Morphological and genetic results were consistent in identifying a separate group in French Polynesia, which we describe here as a new species: the Polynesian anemonefish, Amphiprion maohiensis.